Kepastian Hukum Administratif dalam Penerapan Electronic Traffic Law Enforcement (ETLE) terhadap Pemilik Kendaraan di Wilayah Polda Sulawesi Tengah - Arfiyan Sidrajat , Kurniawan; Syachdin, Syachdin; Ansar, Ansar (Universitas Jambi, Fakultas Hukum, 2026)
The implementation of Electronic Traffic Law Enforcement (ETLE) reflects a digital transformation in traffic law administration aimed at enhancing efficiency, transparency, and accountability. However, the system raises legal concerns related to administrative responsibility based on vehicle registration data, particularly when ownership records are outdated. This study aims to examine administrative legal protection for registered vehicle owners within the ETLE system in the jurisdiction of the Central Sulawesi Regional Police. This research employs a normative juridical method using statute and conceptual approaches. The findings reveal that reliance on registration-based data may lead to administrative inaccuracies and legal uncertainty for vehicle owners. In addition, the lack of integrated data verification and limited access to objection mechanisms weakens administrative legal protection. Therefore, strengthening administrative safeguards requires integrated inter-agency data systems, accessible verification and objection procedures, and improved regulatory governance to ensure fairness and legal certainty in ETLE implementation.